Life cycle inventory data for banana-fiber-based biocomposite lids - Rodríguez, L. Joana (Data Brief, 2020)
This data article is related to the research article “Comparative life cycle assessment of coffee jar lids made from biocomposites containing poly (lactic acid) and banana fiber”. The article reports the model parameters used to construct each stage and unit process inventory of the life cycle of coffee jar lids, and the subsequent inventories of the investigated system. It also contains details of calculations and descriptions of inventory uncertainties. Primary data were obtained from lab-scale and pilot-scale tests during product preparation. Secondary data collection was based on detailed review of related international and regional literature, databases and recognized web sites. The data presented here can be used by future life cycle assessment studies on natural fiber composites in packaging applications.